Reduced cardiorespiratory fitness in adult survivors of childhood acute lymphoblastic leukemia. Issue 8 (15th February 2013) - Tonorezos, Emily S.; Snell, Peter G.; Moskowitz, Chaya S.; Eshelman‐Kent, Debra A.; Liu, Jennifer E.; Chou, Joanne F.; Smith, Stephanie M.; Dunn, Andrea L.; Church, Timothy S.; Oeffinger, Kevin C.
Abstract Background Adult survivors of childhood acute lymphoblastic leukemia (ALL) are at increased cardiovascular risk. Studies of factors including treatment exposures that may modify risk of low cardiorespiratory fitness in this population have been limited. Procedure To assess cardiorespiratory fitness, maximal oxygen uptake (VO2max) was measured in 115 ALL survivors (median age, 23.5 years; range 18–37). We compared VO2max measurements for ALL survivors to those estimated from submaximal testing in a frequency‐matched (age, gender, race/ethnicity) 2003–2004 National Health and Nutritional Examination Survey (NHANES) cohort. Multivariable linear regression models were constructed to evaluate the association between therapeutic exposures and outcomes of interest. Results Compared to NHANES participants, ALL survivors had a substantially lower VO2max (mean 30.7 vs. 39.9 ml/kg/min; adjusted P < 0.0001). For any given percent total body fat, ALL survivors had an 8.9 ml/kg/min lower VO2max than NHANES participants. For key treatment exposure groups (cranial radiotherapy [CRT], anthracycline chemotherapy, or neither), ALL survivors had substantially lower VO2max compared with NHANES participants (all comparisons, P < 0.001). Almost two‐thirds (66.7%) of ALL survivors were classified as low cardiorespiratory fitness compared with 26.3% of NHANES participants (adjusted P < 0.0001). In multivariable models including only ALL survivors, treatment exposures were modestly associated with VO2max. Among females, CRT was associated with low VO2max (P = 0.02), but anthracycline exposure was not (P = 0.58). In contrast, among males, anthracycline exposure ≥100 mg/m2 was associated with low VO2max (P = 0.03), but CRT was not (P = 0.54). Conclusion Adult survivors of childhood ALL have substantially lower levels of cardiorespiratory fitness compared with a similarly aged non‐cancer population. Pediatr Blood Cancer 2013;60:1358–1364. © 2013 Wiley Periodicals, Inc.